Filial piety in Chinese Buddhism - Guang, Xing (Peter Lang, 2022)
Foreword / by Professor Timothy H. Barrett -- Introduction -- Filial Piety in Early Buddhism -- Early Buddhist and Confucian Concepts of Filial Piety: A Comparative Study -- The Spread of the Buddhist Teaching of Filial Piety during the Six Dynasties: A Study Based on the Shanzi Jing and the Yulanpen Jing -- Buddhist Response to Confucian and Daoist Criticism of Filial Piety -- "Filial Piety are Precepts": Chinese Buddhist Reinterpretation of Buddhist Precepts -- A Study of the Apocryphal Text: Fumu Enzhong Jing -- A Study of Repaying the Four Kinds of Compassion -- Qisong's Xiaolun: A Study and Critical Translation -- Conclusion -- Bibliography -- Index.